HUBUNGAN ANTARA PERSEPSI KLIEN TENTANG KEMAMPUAN PERAWAT DALAM MELAKSANAKAN KOMUNIKASI TERAPAEUTIK DENGAN KEPUASAN KLIEN DI RUANG UMAR RUMAH SAKIT ROEMANI SEMARANG - Endang Supriyanti, Teguh Budianto (STIKES Widya Husada Semarang, 2010)
Nursing service is an indicator of qualified health service and has a role in determining the level of client satisfaction. Therapeutic communication is an approach method of nursing service by making relation between nurse and client which determining plan of action and cooperation in order to fulfill client need. Because of that, therapeutic communication is hoped to increase professional relation between nurse and client so the client satisfaction can be fulfilled. This research has aim to find out relation between client perception about nurse ability in executing therapeutic communication and client satisfaction in the Umar room of Roemani Hospital, Semarang. Descriptive Correlational is used as the design of this research with cross sectional research. The sample is taken by giving questioner to 50 clients who has been looked after in Umar room of Roemani hospital, Semarang with length of care minimal 2 x 24 hours on January 15 â 29, 2009. Normality of data is tested withÂ Kolmogorov smirnov test, whereas the hypothesis test used Pearson product moment correlation test. The client perception about the nurse ability in executing therapeutic is considered average by client as 52% with mean 42,12 and deviation standard 8,45. Whereas; the level of client satisfaction is in average level as 70% with mean 41,94 and deviation standard 5,77. There is a significant relation between client perceptions about nurse ability in executing therapeutic and the client satisfaction in the Umar room of Roemani hospital, Semarang Do hope the nurse has a knowledge and a high willingness in executing therapeutic communication especially in responding to clientâs complaint. Keywords : Perception, Therapeutic Communication and Client Satisfaction